Mitochondrial Respiration Is Reduced in Atherosclerosis, Promoting Necrotic Core Formation and Reducing Relative Fibrous Cap Thickness. Issue 12 (December 2017) - Yu, Emma P.K.; Reinhold, Johannes; Yu, Haixiang; Starks, Lakshi; Uryga, Anna K.; Foote, Kirsty; Finigan, Alison; Figg, Nichola; Pung, Yuh-Fen; Logan, Angela; Murphy, Michael P.; Bennett, Martin
Abstract : Objective—: Mitochondrial DNA (mtDNA) damage is present in murine and human atherosclerotic plaques. However, whether endogenous levels of mtDNA damage are sufficient to cause mitochondrial dysfunction and whether decreasing mtDNA damage and improving mitochondrial respiration affects plaque burden or composition are unclear. We examined mitochondrial respiration in human atherosclerotic plaques and whether augmenting mitochondrial respiration affects atherogenesis. Approach and Results—: Human atherosclerotic plaques showed marked mitochondrial dysfunction, manifested as reduced mtDNA copy number and oxygen consumption rate in fibrous cap and core regions. Vascular smooth muscle cells derived from plaques showed impaired mitochondrial respiration, reduced complex I expression, and increased mitophagy, which was induced by oxidized low-density lipoprotein. Apolipoprotein E–deficient (ApoE −/− ) mice showed decreased mtDNA integrity and mitochondrial respiration, associated with increased mitochondrial reactive oxygen species. To determine whether alleviating mtDNA damage and increasing mitochondrial respiration affects atherogenesis, we studied ApoE −/− mice overexpressing the mitochondrial helicase Twinkle (Tw + /ApoE −/− ). Tw + /ApoE −/− mice showed increased mtDNA integrity, copy number, respiratory complex abundance, and respiration. Tw + /ApoE −/− mice had decreased necrotic core and increased fibrous cap areas, and Tw + /ApoE −/− bone marrow transplantation also reduced core areas. Twinkle increased vascular smooth muscle cell mtDNA integrity and respiration. Twinkle also promoted vascular smooth muscle cell proliferation and protected both vascular smooth muscle cells and macrophages from oxidative stress–induced apoptosis. Conclusions—: Endogenous mtDNA damage in mouse and human atherosclerosis is associated with significantly reduced mitochondrial respiration. Reducing mtDNA damage and increasing mitochondrial respiration decrease necrotic core and increase fibrous cap areas independently of changes in reactive oxygen species and may be a promising therapeutic strategy in atherosclerosis. Abstract : Supplemental Digital Content is available in the text.